41 Global and interprofessional tracheostomy education: the development and validation of an interactive webinar series for the global community. (31st October 2017) - Wilson-Jeffers, Rachel; Bergman, Lina; Swords, Chloe; Morris, Linda; Randall, Diane; Arora, Asit
Abstract : Background: Caring for patients with tracheostomies involves the collaboration of multiple medical teams and caregivers. Regarding tracheostomies, the 2014 National Confidential Enquiry into Patient Outcome and Death report illustrated a complication rate of 25%. This project aimed to facilitate education around tracheostomy care to improve patient safety within the global inter-professional medical community. Methods: The Global Tracheostomy Collaborative (GTC) led an international series of live, interactive, hour-long webinars. Global experts, including otolaryngologists, specialist nurses, speech therapists, caregivers and patients, conducted four webinars covering various aspects of tracheostomy care. To assess and improve the educational benefit, standardised pre- and post-webinar surveys were conducted. Results: Participants completed 209 pre-evaluation surveys, and 107 post-evaluation surveys. Overall, feedback illustrated the webinars to be informative and valuable. 86% (n=92) of participants would recommend attending the series to colleagues, and 83% (n=89) intended to integrate the learned concepts into their clinical practice. A significant gain in confidence was reported regarding various aspects of tracheostomy care encountered on a daily basis (p<0.05). Conclusions: A unique aspect of this global webinar series is the ability for caregivers and medical professionals to ask questions to and learn from experts and clinician leaders in different countries. This study demonstrates that the development of global education programs is feasible and valuable.